Analysis of Financial Performance at Cooperative : The role of Liquidity and Profitability Ratio - Mufida Amalia (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2023)
Assessment of the financial performance of a financial institution can use financial report analysis. With the aim to know how big the financial performance is at the Al hudori Cooperative Prabumulih branch is in good health. This financial performance is reviewed through an analysis of the ratio finances. In this study, researchers used descriptive analysis approach quantitative. Taking research subjects at the Al hudori Cooperative branch of Prabumulih While the object the research taken is the annual report of the Al hudori Cooperative branch of Prabumulih starting from the period 2020–2022 Research conducted shows that the Liquidity Ratio is of the Current Ratio typeprovide quite healthy results for its financial performance, and provide results of financial performanceunhealthy on the type of cash ratio. Profitability Ratio as measured by the type of Return on Equity (ROE)provide results of financial performance in unhealthy conditions, in the type of Return on Assets(ROA) providesfinancial performance results in a fairly healthy condition, and Net Profit Marginwhich provides financial performance results in a very healthy condition. With Thus the results of the financial performance analysis on the financial reports of the Prabumulih branch of the Al Hudori Cooperative throughi nancial ratio analysis is quite good even though the performance of cooperatives experiences every year decline and fluctuation.